Third shift labor of advanced career learners: Growing the adult education field - Tulare W. Park; Carol Rogers-Shaw; Dorca Kisare-Ressler (Adult Education Research Conference, 2020)
This paper explores the literature on advanced-career adult learners pursuing graduate education on the “third shift”, which begins after daily work and family obligations are completed (Kramarae, 2001, p. 3). The purpose is to explain the unique characteristics of these learners and the ways in which educators can offer support so they are successful and able to return to practice as adult educators themselves to grow the field of adult education.
Keywords: third shift; advanced-career; graduate education.